Development of Staffing Procedure in Human Resource Department of XYZ Corporation at Caloocan City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
XYZ Company is a corrugated box manufacturing corporation located at 648 Llano Rd. in Caloocan City. The company currently faces challenges with its staffing procedure, prompting researchers to suggest improvements in the staffing process and office layout design to enhance efficiency. The researchers conducted qualitative research to gather information, interviewing the Director of the Human Resources department at XYZ Corporation. The researchers came to the conclusion that absenteeism is a common problem for the HR department and that the office layout significantly affects overall staff productivity based on their findings. To address these concerns, the researchers proposed implementing the following changes at XYZ: a more spacious office layout to prevent delays and promote efficiency, ergonomics, and incentives to prevent staff absenteeism and confusion about tasks. The researchers believe XYZ Company can improve overall performance by making these improvements.
Keywords: Staffing Procedure; Office Layout; Development; Turn-over process